Grønland og Norge i middelalderen - Bull, Edvard, 1881-1932.; Fiske Icelandic Collection. NIC
I̲n̲ Det norske geografiske selskabs aarbok. XXXI-XXXII. 1919- 1921. -- Kristiania : I kommission hos H. Aschehoug, 1922. Caption title. Includes bibliographical references. Halldór Hermannsson. Cat. of the Icelandic Coll. (1913-1926). Mode of access: Internet.